2012
DOI: 10.1186/1471-213x-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Spiral cleavage and early embryology of a loxosomatid entoproct and the usefulness of spiralian apical cross patterns for phylogenetic inferences

Abstract: BackgroundAmong the four major bilaterian clades, Deuterostomia, Acoelomorpha, Ecdysozoa, and Lophotrochozoa, the latter shows an astonishing diversity of bodyplans. While the largest lophotrochozoan assemblage, the Spiralia, which at least comprises Annelida, Mollusca, Entoprocta, Platyhelminthes, and Nemertea, show a spiral cleavage pattern, Ectoprocta, Brachiopoda and Phoronida (the Lophophorata) cleave radially. Despite a vast amount of recent molecular phylogenetic analyses, the interrelationships of loph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…6.5 ;Merkel et al 2012 ). Gastrulation is preceded by fl attening of the embryo, occurs when the embryo has slightly more than 100 cells, and eventually results in a coeloblastula (Merkel et al 2012 ). This is in accordance with the data provided by Marcus ( 1939 ) on Pedicillina cernua , who found the embryos to gastrulate at around 120 cells.…”
Section: Early Developmentsupporting
confidence: 86%
See 2 more Smart Citations
“…6.5 ;Merkel et al 2012 ). Gastrulation is preceded by fl attening of the embryo, occurs when the embryo has slightly more than 100 cells, and eventually results in a coeloblastula (Merkel et al 2012 ). This is in accordance with the data provided by Marcus ( 1939 ) on Pedicillina cernua , who found the embryos to gastrulate at around 120 cells.…”
Section: Early Developmentsupporting
confidence: 86%
“…Recently, new data have become available on a yet undescribed Loxosomella species employing fl uorescence staining of nuclei and 3D reconstruction of embryogenesis (Figs. 6.3 and 6.4 ;Merkel et al 2012 ). Most authors noted a holoblastic, more or less equal, spiral cleavage pattern, comparable to that of other Spiralia.…”
Section: Early Developmentmentioning
confidence: 69%
See 1 more Smart Citation
“…When cell fates are compared between spiralians, it is often found that the same adult or larval organs in different species arise from the same blastomeres [defined by lineage and relative position in the blastula (Nielsen, 1994;Lyons et al, 2012)]. The first four cell division rounds are synchronous but this synchrony is gradually lost over developmental time and the similarity between groups becomes less obvious (Freeman and Lundelius, 1982;Merkel et al, 2012). In some species with a very derived spiralian cleavage, this synchrony can be lost much earlier (Nielsen, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Such gradients promote asymmetric cell division by a differential binding of the spindle microtubules to the cortex that results in asymmetric pulling forces and a displacement of the contractile ring during cytokinesis (Gilbert and Raunio, 1997;Ren and Weisblat, 2006;Lu and Johnston, 2013). Asymmetric cell division may play a role in generating morphological variation among the spiral cleavage patterns because blastomeres of different relative sizes are placed and compacted in different manners due to cell-cell adhesion (Merkel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%